Playing at the school table: Systematic literature review of board, tabletop, and other analog game-based learning approaches - Sousa, Carla; Rye, Sara; Sousa, Micael; Torres, Pedro Juan; Perim, Claudilene; Mansuklal, Shivani Atul; Ennami, Firdaous (Frontiers in Psychology, 2023)
The unique characteristics of games have led scientific research to increasingly focus on their potential role in learning processes. Currently, their effectiveness in fostering experiential learning and skill acquisition in several areas is already supported by the existing evidence, mainly about the potential of digital games. Paradoxically, the current post-digital era seems to have led to a growing popularity of analog games. The present Systematic Literature Review aimed to map the existing literature on the potential of board, tabletop, or other analog games in learning processes. It intended to systematize the contemporary state of the art (2012–2022) around the pedagogical role of these games, their effectiveness, the promoted learning outcomes, the methodological aspects of the interventions, the used games—including mechanics and other characteristics—and the current discussions around inclusion and accessibility in analog game-based learning. Adopting the PRISMA methodology, we searched ACM Digital Library, EBSCO, ERIC, Scopus—Elsevier, and Web of Science databases, as well as other peer-reviewed “grey literature” sources. The search resulted in an initial sample of 2,741 articles that was then screened by inclusion and exclusion criteria previously defined according to the research objectives. We obtained a final sample of 45 articles. To formulate the mapping of existing research, these studies were analyzed using a combination of statistical, content, and critical analysis procedures. The obtained results support the role of board, tabletop, and other analog games in educational contexts—based on their educational potential—with a broad range of knowledge, cognitive, and psychological outcomes. The study also emphasized the relevance of these games in the promotion of soft skills and other aspects typically associated with meaningful learning, such as engagement, satisfaction, flexibility, and freedom of experimentation. However, important limitations were found in a fair amount of the pedagogical approaches studied, which can be mostly attributed to the low prevalence of modern board games that relate what is intended to be learned to aspects of game design and have little to no consideration of accessibility and inclusion aspects in these studies.